Clinico-Biochemical Abnormalities in Hospitalized Neonates with or without Seizure - Muhammad Masuduzzaman, Shah; Islam, Md Nazrul; Mollah, Md Abid Hossain; Hoque, Mohammad Azizul; Hossain, Md Anwar; Islam, Md Saiful (Medicine Today, 2020)
Introduction: To determine the clinical types and etiological factors and to assess the biochemical abnormalities in neonates with seizure. Materials and Methods: This was a Cross-sectional, comparative hospital based study. Ninety neonates, age up to 28 days of both sexes were evaluated for clinical types, etiological factors and biochemical abnormalities with seizure and compared with those having no seizures. The variables were analyzed using student t- test. All the data was processed and analyzed by computer software SPSS version 15.0. Level of significance was considered as p value less than 0.05. Results: Most of the neonates having seizures (72%) within 3 days of life. The seizures were common in male babies (62%). 35% of the mother of baby with seizure gave history of prolonged labour. HIE was diagnosed 56.67% neonates with seizure whereas infection were found in 25% cases with seizure. Among the seizure subtypes, subtle seizures were 58% followed by clonic seizures 30%. Significant biochemical changes we found in 43.34% of neonates with seizures. Hypocalcemia (46%) was most common followed by hypoglycemia(38%). Conclusion: Hypoxic ischemic encephalopathy was the commonest cause of neonatal seizure followed by neonatal infections including meningitis and sepsis.. Biochemical abnormalities are more common in neonates with seizure than neonates free from seizure. Among the biochemical abnormalities hypocalcaemia and hypoglycemia occurs most commonly followed by hyponatraemia and hypomagnesaemia. Medicine Today 2020 Vol.32(1): 37-41